Histopathology of Cutaneous Inflammatory Disorders in Children. (April 2018) - Hsi, Andy C; Rosman, Ilana S
Inflammatory dermatoses encompass a variety of histologic patterns that affect different portions of the skin. In spongiotic, psoriasiform, lichenoid, pityriasiform, and blistering disorders, there are predominately epidermal and junctional activities with variable superficial dermal inflammation. Hypersensitivity reactions can show either epidermal or mostly dermal changes depending on whether the exposure of the exogenous allergen occurs through an external or internal route, respectively. Exceptions include erythema multiforme and Stevens-Johnson syndrome/toxic epidermal necrolysis, where the etiology is often due to infection or ingested medications, but the histologic features are almost exclusively confined to the epidermis and dermoepidermal junction. Autoimmune disorders are unique in that lesions typically incorporate a mixture of epidermal and dermal inflammatory patterns with periadnexal inflammation, while the vast majority of vasculitis/vasculopathy and alopecia have changes limited to only the vessels and hair follicles, respectively. It is critical to recognize that a relatively limited number of histologic patterns are seen in a large array of clinical entities. Therefore, clinicopathologic correlation and careful examination of histologic details are of the utmost importance when evaluating skin biopsies for inflammatory disorders.